2022
DOI: 10.1161/atvbaha.122.317643
|View full text |Cite
|
Sign up to set email alerts
|

Aging Alters the Aortic Proteome in Health and Thoracic Aortic Aneurysm

Abstract: Background: Aging enhances most chronic diseases but its impact on human aortic tissue in health and in thoracic aortic aneurysms (TAA) remains unclear. Methods: We employed a human aortic biorepository of healthy specimens (n=17) and those that underwent surgical repair for TAA (n=20). First, we performed proteomics comparing aortas of healthy donors to aneurysmal specimens, in young (ie, <60 years of age) and old (ie, ≥60 years of age) subjects. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Probably, a synergistic action of all these elements reflects the different AAA phenotypes associated with BAV, as stressed in our works, than those detected in TAV individuals [4,10,12]. Differently, TAV subjects show a more advanced age of AAA onset, about versus the 70-75 years, and a pathogenesis more related to vascular aging and the resultant remodeling and degeneration process associated with a preeminent fibrosis, that significantly reduces the probability of AAA progression in dissection and rupture [2,[13][14][15][16][17]. Precisely, a typical vascular remodeling and degeneration, accompanied by wound healing associated with a significant increase of circulating EPC levels [9,11], tissue expression of TGF-β and Smad-3 [18][19][20][21] consequent inflammation, endothelial-to-mesenchymal transition (EndMT) [22][23][24] and fibrosis [25], embody aorta dilation, or better, AAA disease, in TAV patients.…”
Section: Introductionmentioning
confidence: 55%
“…Probably, a synergistic action of all these elements reflects the different AAA phenotypes associated with BAV, as stressed in our works, than those detected in TAV individuals [4,10,12]. Differently, TAV subjects show a more advanced age of AAA onset, about versus the 70-75 years, and a pathogenesis more related to vascular aging and the resultant remodeling and degeneration process associated with a preeminent fibrosis, that significantly reduces the probability of AAA progression in dissection and rupture [2,[13][14][15][16][17]. Precisely, a typical vascular remodeling and degeneration, accompanied by wound healing associated with a significant increase of circulating EPC levels [9,11], tissue expression of TGF-β and Smad-3 [18][19][20][21] consequent inflammation, endothelial-to-mesenchymal transition (EndMT) [22][23][24] and fibrosis [25], embody aorta dilation, or better, AAA disease, in TAV patients.…”
Section: Introductionmentioning
confidence: 55%
“…There are strong risk factors for TAA, including genetic determinants, such as the Marfan syndrome and bicuspid aortic valves, as well as hemodynamic determinants, such as hypertension and inflammatory diseases of the aorta. [5][6][7] The article by Tyrrell et al 4 reports on proteomic comparisons between 4 cohorts of patients: healthy young and healthy elderly individuals and young and older patients with TAA. This allows a unique dissection of the distinct impact of age and disease.…”
Section: See Accompanying Article On Page 1060mentioning
confidence: 99%
“…22 Disease states, such as atherosclerosis and diabetes, are known to counterregulate antioxidant mechanisms, 34,37,38 and, together with altered mitochondrial and immune function, this can lead to an overall increase in inflammation in the vessel. 36,39 Increased inflammation has been linked to atherosclerotic plaque rupture 40 and aortic aneurysms, 36,41 and, indeed, Tyrrell et al 4 found differences in protein expression in aged patients with TAA, reflecting changes in mitochondrial function and repair, as well as reactive oxygen species pathways.…”
mentioning
confidence: 99%
See 2 more Smart Citations